Endocan - a potential diagnostic marker for early onset sepsis in neonates - Zonda, Gabriela Ildiko; Zonda, Radu; Cernomaz, Andrei Tudor; Paduraru, Luminita; Avasiloaiei, Andreea Luciana; Grigoriu, Bogdan Dragos (The Journal of Infection in Developing Countries, 2019)
Introduction: Neonatal early onset sepsis assessment is based on the history of pregnancy and delivery and nonspecific clinical signs. None of the biomarkers currently in use for clinical practice has adequate prognostic value, so it is not possible to clearly distinguish neonates with culture-proven sepsis from those with only risk factors or clinical suspicion. Endocan is an endothelial mediator involved in the inflammatory response that is present in low concentrations in the serum of healthy subjects, and in much higher concentrations in patients with SIRS and septic shock. The purpose of this study is to evaluate the utility of serum endocan serum levels as a biomarker for the diagnosis of neonatal early onset sepsis (EOS). Methodology: Serum endocan concentration was measured in newborns with clinical suspicion of EOS admitted to the Neonatal Intensive Care Unit on day 1, 3 and 7. Results: Serum endocan levels were significantly increased in septic compared to non-septic neonates in the early stages of sepsis (2.43 ± 0.95 vs. 1.77 ± 0.57, p = 0.004), continued to rise up to 72 hours from onset and then decreased by the seventh day under treatment. Conclusions: These results suggest a potential role for endocan as an early marker for diagnosis and follow-up in neonatal EOS. Studies on a larger number of cases are needed in order to establish the practical utility of this molecule as a diagnostic tool for clinical practice.